Q: -2t - 7 6t - 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6t - 5t - 6 = (3t + 2)(2t - 3)

6t - 4x

7

2t+3 = -11 Subtract 3 from both sides: 2t+3-3 = -11-3 2t = -14 Divide both sides by 2 in order to find the value of t: t = -7

3t + 7 = 2t - 5 3t = 2t - 12 t = -12

Related questions

6t -2t + 5u = 4t - 5u

For "6t - (2t2)", it is not reducible. For "(6t - 2t2)", it is 16t2

6t2+17t+7 = (3t+7)(2t+1) when factored

4

2t-3-3 = 7 2t = 7+6 2t = 13 t = 6.5

6t - 5t - 6 = (3t + 2)(2t - 3)

t=3/2 or t=2 1/2

6t - 4x

6t + 7 when t = -3 is 6*(-3) + 7 = -18 + 7 = -11

7

8t + 5 = 6t + 1,subtract 6t an 5 from each side,2t = -4t = -2Checking, 8t + 5 = -16 + 5 = -11 and 6t +1 = -12 + 1 = -11

If that's + 7t, the answer is (3t + 5)(2t - 1) If that's - 7t, the answer is (3t - 5)(2t + 1)